2020
DOI: 10.1017/s0007114520000331
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rumen-protected folic acid and betaine supplementation on growth performance, nutrient digestion, rumen fermentation and blood metabolites in Angus bulls

Abstract: This study evaluated the effects of rumen-protected folic acid (RPFA) and betaine (BT) on growth performance, nutrient digestion and blood metabolites in bulls. Forty-eight Angus bulls were blocked by body weight and randomly assigned to four treatments in a 2 × 2 factorial design. BT of 0 or 0·6 g/kg DM was supplemented to diet without or with the addition of 6 mg/kg DM of folic acid from RPFA, respectively. Average daily gain increased by 25·2 and 6·29 % for addition of BT without RPFA and with RPFA, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 31 publications
(76 reference statements)
2
23
0
Order By: Relevance
“…Meanwhile, Shah et al [ 26 ] reported that betaine supplementation (15 g/d) in dairy cow feed increased the total VFA and acetic acid proportion but decreased the propionic acid proportion; therefore, it is possible that betaine is metabolized in the rumen and converted to acetate [ 16 ]. Wang et al [ 17 ] noted that betaine in the rumen could be metabolized into acetate and increase the concentration of acetate at high-dose supplementation levels (100 g/d).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, Shah et al [ 26 ] reported that betaine supplementation (15 g/d) in dairy cow feed increased the total VFA and acetic acid proportion but decreased the propionic acid proportion; therefore, it is possible that betaine is metabolized in the rumen and converted to acetate [ 16 ]. Wang et al [ 17 ] noted that betaine in the rumen could be metabolized into acetate and increase the concentration of acetate at high-dose supplementation levels (100 g/d).…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al [ 16 ] found that betaine supplementation at 15 g/day increases the feed intake, milk yield, and levels of lactose and protein in the milk of dairy cows. Furthermore, Wang et al [ 17 ] found that adding betaine at 0.6 g/kg DM to feed stimulates growth and nutrient digestion in bulls. Based on the aforementioned research, the combinatorial use of biotin, betaine, and chromium (BBC) seems to be a promising approach towards improving feed utilization and nutrient metabolism, resulting in enhanced growth performance.…”
Section: Introductionmentioning
confidence: 99%
“…The higher dressing and meat percentage following RPFA addition to the maternal and/or lambs' diets indicated that protein deposition was promoted by RPFA supplementation. The results might be due to the elevation in the apparent total tract digestibility of crude proteins (9) and hepatic gene expression responsible for protein synthesis, because according to an earlier study dietary RPFA addition could stimulate the transfer efficiency of methyl groups and the biosynthesis of amino acids, thereby facilitating protein synthesis (25) . In addition, La et al (26) demonstrated that hepatic gene expression related to protein synthesis was up-regulated by RPFA added to the diet of dairy calves.…”
Section: Slaughter Performancementioning
confidence: 99%
“…These results suggested that the development of the stomach in lambs was stimulated by RPFA added to the maternal and/or the lambs' diets. Stomach development is due to an increase in ruminal fermentation products, such as acetate, propionate and butyrate, etc (25) . Li et al (9) found that the ruminal total volatile fatty acids concentration and molar proportions of acetate and butyrate increased with RPFA addition to the maternal diet, and molar proportions of acetate elevated when RPFA was added to the lambs' diet.…”
Section: Stomach and Intestine Characteristicsmentioning
confidence: 99%
“…In ruminants, supplemental BET plays its role in two ways (Hall et al 2016). Firstly, it is degraded in the rumen to a variable extent and utilized by the rumen microbes resulting in enhanced fermentation activity and increased production of short-chain volatile fatty acids which are a major source of energy for ruminants (Wang et al 2020a). Under normal conditions, the acetic acid is the ultimate end product of BET but under stressed and hyperosmotic conditions the end product of BET degradation is propionate which is a glycogenic precursor and an energy source.…”
Section: Introductionmentioning
confidence: 99%